Molecular study of drought response in the Mediterranean conifer Pinus pinaster Ait.: Differential transcriptomic profiling reveals constitutive water deficit‐independent drought tolerance mechanisms. Issue 18 (31st August 2020) - de María, Nuria; Guevara, María Ángeles; Perdiguero, Pedro; Vélez, María Dolores; Cabezas, José Antonio; López‐Hinojosa, Miriam; Li, Zhen; Díaz, Luís Manuel; Pizarro, Alberto; Mancha, José Antonio; Sterck, Lieven; Sánchez‐Gómez, David; et al.
Abstract: Adaptation of long‐living forest trees to respond to environmental changes is essential to secure their performance under adverse conditions. Water deficit is one of the most significant stress factors determining tree growth and survival. Maritime pine ( Pinus pinaster Ait.), the main source of softwood in southwestern Europe, is subjected to recurrent drought periods which, according to climate change predictions for the years to come, will progressively increase in the Mediterranean region. The mechanisms regulating pine adaptive responses to environment are still largely unknown. The aim of this work was to go a step further in understanding the molecular mechanisms underlying maritime pine response to water stress and drought tolerance at the whole plant level. A global transcriptomic profiling of roots, stems, and needles was conducted to analyze the performance of siblings showing contrasted responses to water deficit from an ad hoc designed full‐sib family. Although P. pinaster is considered a recalcitrant species for vegetative propagation in adult phase, the analysis was conducted using vegetatively propagated trees exposed to two treatments: well‐watered and moderate water stress. The comparative analyses led us to identify organ‐specific genes, constitutively expressed as well as differentially expressed when comparing control versus water stress conditions, in drought‐sensitive and drought‐tolerant genotypes. Different response strategies can point out, with tolerant individuals being pre‐adapted for coping with drought by constitutively expressing stress‐related genes that are detected only in latter stages on sensitive individuals subjected to drought. Abstract : The manuscript presents the transcriptome of maritime pine trees that show contrasted response to drought. Comparison of transcriptomic profiles at the organ level allowed to identify organ‐specific and genotype‐specific transcripts as well as differentially expressed genes between organs, genotypes, and treatments. The results also point out to different response strategies, with tolerant plants pre‐adapted for coping with drought by expressing constitutively stress‐related genes that only can be detected in sensitive plants submitted to drought.